Hypoxic Mesenchymal Stem Cells Mitigate UVB-Induced Collagen Loss by Suppressing IL-6 and MMP-3 in a Rat Model - Anindyasarathi, Fitri; Putra, Agung; Sumarawati, Titiek; Setiawan, Eko; Nur (Scripta Medica, 2025)
Background/Aim: Persistent ultraviolet B (UVB) radiation exposure generates oxidative stress, facilitating proinflammatory interleukin-6 (IL-6) cytokine secretion that subsequently activates the matrix metalloproteinase 3 (MMP-3) enzyme, resulting in collagen degradation. Mesenchymal stem cells cultured under hypoxic conditions (HMSCs) demonstrate the capacity to stimulate diverse cytokines and growth factors capable of preventing collagen breakdown. This study aims to evaluate the role of HMSCs administration on MMP-3 and IL-6 levels in a rat model exposed to UVB radiation, which causes collagen loss. Methods: This study was an experimental in vivo study using a post-test-only control group design with a completely randomised method. The study included male Wistar rats aged 2 to 3 months, weighing between 200 and 250 grams. Male Wistar rats were divided into 5 groups: T1 (healthy rats without UVB exposure), T2 (rats exposed to UVB without treatment), T3 (rats subjected to UVB radiation received a 200 μL subcutaneous injection of HA), T4 (rats subjected to UVB radiation received a 2.5 × 105 HMSCs cells subcutaneously) and T5 (rats subjected to UVB radiation received a 5 × 105 HMSCs cells subcutaneously). Analysis of MMP-3 and IL-6 levels was performed using the ELISA method. Results: Administration of HMSCs at doses of 2.5 × 105 and 5 × 105 cells significantly decreased IL-6 levels to 66.22 and 42.19 pg/mL, respectively. HMSCs administration also significantly decreased MMP-3 levels, with a dose of 5 × 105 cells reducing MMP-3 levels to 3329.00 pg/mL. Conclusion: HMSCs improve the condition of collagen loss in the skin due to UVB radiation exposure through inhibition of IL-6 and MMP-3.